Effect of storage temperature and bean genotypes on the resistance to Acanthoscelides obtectus (Say) (Coleoptera : Bruchidae) - Baldin, ELL; Lara, F. M. (Entomological Soc Brasil, 2004)
Aiming to evaluate the effect of different temperatures of storage and bean genotypes, Phaseolus vulgaris L., on the expression of resistance to the bean weevil, Acanthoscelides obtectus (Say), tests were carried out with the genotypes ArC.1S, Arc.1, Arc.2, Arc.4 and Carioca Pitoco. Grains of Arc.1S and Arc.2 expressed resistance to A. obtectus at 20degreesC, 25degreesC and 30degreesC; the resistance of Arc.1 was reduced as the storage temperature increased from 25degreesC to 30degreesC. The interaction genotypes x temperatures was significant, indicating that the increase of temperature affects the expression of resistance. The 20degreesC temperature was the most suitable to allow bean genotypes to be discriminate in terms of resistance.
Keywords: Insecta; Phaseolus vulgaris; bean weevil; plant resistance; temperature effect